Account of an Informed Bat Exclusion at the Temple of Deir el-Shelwit, Luxor, Egypt. (May 2013) - Porter, Jennifer Herrick; Corda, Katey
<x content-type="archive" xml:space="preserve">Abstract</x> The conservation of the painted Roman-era reliefs in the temple of Deir el Shelwit in Luxor, Egypt, was recently initiated by the American Research Center in Egypt (ARCE). As a critical step in a series of preliminary preventive conservation measures undertaken at the temple, a resident bat colony was excluded to control further deterioration of the painted reliefs and stone fabric (Figure 1). In consultation with a bat biologist, a comprehensive humane, low-tech emergency exclusion programme was designed and implemented, which included roost location, behavioural surveys, species identification, sealing of building openings, bat exclusion and the design of an alternate roost site. This programme may serve as a useful example for other conservation projects in Luxor, since it provides much-needed information on the behaviour of local bats, as well as relevant insights gained from the exclusion procedure.